Teologi Sunni: Perbedaan Teologi Asy’ari dan Maturidi - Istifarin, Nur Annisa; Nurnajib, Zavira Orcana; Alfani, Mukhammad; Vidityas, Siti (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
Ash'ariyah is a traditional theology of thought which was composed by Abu Hasan Al-Asy'ari (935) as a reaction to Mu'tazilah theology. The Ash'ari theology of thought is generally embraced by Muslims who adhere to the Sunni theology of thought. Maturidiyah is a theology of kalam which is based on the use of arguments and theorem of aqli kalami is also a theology in Islam which is a teaching of rational technology. This genre was founded by Abu Mansur Muhammad bin Muhammad bin Mahmud Almaturidi. In the classification of Islamic theology, Asy'aria and Maturidi are called Ahl Sunnah wal Jamaah. This study uses the method of literature study, aims to explain and describe how the history of the birth of Asy'ariyah and its thoughts. Al-Asy'ari concluded that reason and proof or texts are equally important. Meanwhile, Maturidi gives great authority to human reason, without exaggerating or exceeding limits.